Dynamics of vegetative growth of Hevea brasiliensis in determining tapping norms - Obouayeba S; Boa D; Dian K; Gohet E; Keli Z J; Ouattara N (Journal of Rubber Research, 2000)
A study to determine norms for the tapping of Hevea brasiliensis was carried out in Cote dIvoire. This was aimed at defining age and minimum girth for the panel opening of Hevea which takes into account the notion of physiological maturity. The modelled vegetative growth curve is a sigmoid with a change in the gradient at the third pahse which is a plausible solution to the problems of this study. Analysis of growth dynamics shows that this point hardly varies, irrespective of the growth class of the clone, and takes place at the sixth year after planting. In addition, several observations on the growth of Hevea under different conditions support the proposal of a minimum tapping girth linked with the growth class, thus combining the notion of age and size.
Keywords: Tapping norms; Vegetative growth